2015
DOI: 10.1063/1.4905228
|View full text |Cite
|
Sign up to set email alerts
|

The study of electromagnetic cusp solitons

Abstract: The formation of a cusp structure in the envelope of electromagnetic solitons for electron-ion plasma at the ion wave breaking point has been shown by Farina and Bulanov [Phys. Rev. Lett. 86, 5289 (2001)]. The analytical form of the cusp structure has been obtained here. The analytical form of the cusp is shown to compare well with the exact numerically obtained solutions. Such cusp solitons occurring at the ion wave breaking point may have relevance to ion acceleration mechanism. In an effort towards studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Next, for the modulational instabilities of EMWs associated with the nonresonant electron and ion density perturbations, we retain both D ± ( = 0) and S R,B ( = 0) in Eqs. (25) and (26). Thus, we obtain [2]…”
Section: Derivation and Analysis Of Nonlinear Dispersion Relationmentioning
confidence: 96%
See 2 more Smart Citations
“…Next, for the modulational instabilities of EMWs associated with the nonresonant electron and ion density perturbations, we retain both D ± ( = 0) and S R,B ( = 0) in Eqs. (25) and (26). Thus, we obtain [2]…”
Section: Derivation and Analysis Of Nonlinear Dispersion Relationmentioning
confidence: 96%
“…with v g = k 0 /ω 0 denoting the dimensionless group velocity of the EMW pump, ω 0 = 1 + k 2 0 is the pump frequency, and δ = K 2 /2ω 0 is the dimensionless nonlinear frequency shift. The dispersion relations (25) and (26) In the absence of the pump, S R = S B = 0, and we have the following dispersion relations for electron (Langmuir) and ion plasma oscillations.…”
Section: Derivation and Analysis Of Nonlinear Dispersion Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been found that arising of density bursts in the trailing edge of the modulated structures is demonstration of an instability which is arising from a nonlinear phase mixing mechanism [15]. Verma et al [16] have done analytical studies on electromagnetic soliton, where the analytical form of the cusp structure in the envelope of electromagnetic soliton at the ion wave breaking point for electron-ion plasma has been obtained. In this work, the time evolution studies have also been done to show the survival of these structures for several plasma periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The richness of nonlinear interactions in laser plasma interaction provides a fertile ground for the formation of such structures. For instance, a rich class of one-dimensional nonlinear solitonic structures has been predicted and their stability and interaction have been studied (Kaw, Sen & Katsouleas 1992; Naumova et al 2001 a ; Esirkepov et al 2002; Poornakala et al 2002 a , b ; Shukla & Eliasson 2005; Romagnani et al 2010; Sundar et al 2011; Verma et al 2015, 2017). An approximate fluid model electron magnetohydrodynamics (EMHD) (Biskamp, Schwarz & Drake 1996; Isichenko & Marnachev 1987) describing plasma response at fast electron time scales provides for nonlinear coherent solutions comprising of rotating electron currents in two dimensions.…”
Section: Introductionmentioning
confidence: 99%